2019
DOI: 10.1002/iroh.201901991
|View full text |Cite
|
Sign up to set email alerts
|

Does the world need faunists? Based on rotifer (Rotifera) occurrence reflections on the role of faunistic research in ecology

Abstract: Most faunistic studies of large‐scale patterns concern terrestrial vertebrates, whereas smaller organisms, and in particular, freshwater invertebrates like rotifers receive less attention. As a result, the “rotiferologists” effect”, that is sampling intensity, is among the most influential factors observed, globally or locally, on species richness. Because there are many more small, isolated patches of habitats available to the specialist species, greater specialization has occurred in those forms than in ubiq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…The primary objective of faunistic studies are to document and record medical and economic important species of insects ( Ježek et al 2021 , Shehzad et al 2017 ). These studies are crucial for assessing the abundance of species found within a specific geographical area and monitoring the long-term shifts in population trends and diversity ( Ejsmont-Karabin 2019 , Shamna et al 2023 ). This has become particularly important to protected areas like Juniperus Ziarat, which hold immense biodiversity of significance, but has not received sufficient research attention for certain insect groups.…”
Section: Introductionmentioning
confidence: 99%
“…The primary objective of faunistic studies are to document and record medical and economic important species of insects ( Ježek et al 2021 , Shehzad et al 2017 ). These studies are crucial for assessing the abundance of species found within a specific geographical area and monitoring the long-term shifts in population trends and diversity ( Ejsmont-Karabin 2019 , Shamna et al 2023 ). This has become particularly important to protected areas like Juniperus Ziarat, which hold immense biodiversity of significance, but has not received sufficient research attention for certain insect groups.…”
Section: Introductionmentioning
confidence: 99%
“…Rotifers are considered to be a valuable tool in environmental assessments, mainly because they are quite abundant, and thus, are an important part of most non-marine food webs [4,5]. In addition, rotifers are generally cosmopolitan, and their distribution is generally limited by environmental conditions, but may also be limited by biogeographic barriers [6,7]. It is also known that because of their evolutionary adaptations, rotifers segregate according to the specificity of habitats [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Rotifers, on the other hand can be kept in laboratory cultures. However, they only inhabit aquatic ecosystems (Ejsmont-Karabin, 2019), whereas nematodes can inhabit a variety of ecosystems (terrestrial, freshwater, marine) providing a more comprehensive overview on the evolution of asexuality.…”
Section: Introductionmentioning
confidence: 99%
“…The copyright holder for this preprint (which was not certified by this version posted September 17, 2022. ; https://doi.org/10.1101/2022.09.15.508068 doi: bioRxiv preprint i i i i i i i i kept in laboratory cultures. However, they only inhabit aquatic ecosystems (Ejsmont-Karabin, 2019), whereas nematodes can inhabit a variety of ecosystems (terrestrial, freshwater, marine) providing a more comprehensive overview on the evolution of asexuality.…”
mentioning
confidence: 99%